2010
DOI: 10.1016/j.intman.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Business groups' outward FDI: A managerial resources perspective

Abstract: Outward FDI strategies are driven by firms' resource endowments, which in turn are conditioned by their home environment. In emerging economies, thus, the pattern of outward FDI is shaped by local firms' idiosyncratic contexts and the resources that these firms developed to fit the contexts. This includes business groups, a dominant organizational form in many emerging economies, competing with context-bound resources. When they wish to transcend their home context, they need internationally valuable resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 81 publications
3
129
1
Order By: Relevance
“…Thus, home market conditions shape the FSAs of EMNEs (Elango & Pattnaik, 2007;Tan & Meyer, 2010;Yiu et al, 2007) and allow the development of bundling skills -some prior to internationalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, home market conditions shape the FSAs of EMNEs (Elango & Pattnaik, 2007;Tan & Meyer, 2010;Yiu et al, 2007) and allow the development of bundling skills -some prior to internationalisation.…”
Section: Discussionmentioning
confidence: 99%
“…It can also transfer other resources internally, such as knowledge, needed to operate internationally. The literature indicates that a firm may internationalise by leveraging group resources (Douma, George, & Kabir, 2006;Guillén, 2003;Tan & Meyer, 2010;Yiu et al, 2005).…”
Section: Business Group Affiliationmentioning
confidence: 99%
“…Research has shown that the demographic and team characteristics of top management teams influence firms' internationalization strategies (Nielsen & Nielsen, 2011). In particular, the international experience of managers is strongly associated with internationalization strategies (Sambharya, 1996;Tan & Meyer, 2010). Through the selection of individuals for leadership roles in a company, owners intentionally or unintentionally shape the firms' strategies.…”
Section: Ownership and Governancementioning
confidence: 99%
“…They can also transfer other resources needed to expand abroad internally, such as knowledge. The literature suggests that firms may internationalise by leveraging group resources (Douma et al 2006;Guillén 2003;Tan and Meyer 2010;Yiu et al 2005). Besides accessing the internal pool of resources, synergy between different subsidiaries of an Indian business group can also facilitate internationalisation of the firm; for instance, synergies between the subsidiaries of Tata group (Mukherjee and Radhakrishnan 2002).…”
Section: India: Domestic Capital Marketmentioning
confidence: 99%
“…Besides accessing the internal pool of resources, synergy between different subsidiaries of an Indian business group can also facilitate internationalisation of the firm; for instance, synergies between the subsidiaries of Tata group (Mukherjee and Radhakrishnan 2002). Business groups are dominant in many emerging economies (Tan and Meyer 2010;Khanna and Palepu 1999;Peng and Heath 1996). Most Indian business groups are diversified across several industries and are highly internationalised at the same time; for instance, Tata group operates in 28 industries and has a presence in about 80 countries (Tata 2012).…”
Section: India: Domestic Capital Marketmentioning
confidence: 99%